2009
DOI: 10.1302/0301-620x.91b5.21878
|View full text |Cite
|
Sign up to set email alerts
|

Nerve reconstruction in patients with obstetric brachial plexus injury results in worsening of glenohumeral deformity

Abstract: Whereas a general trend in the management of obstetric brachial plexus injuries has been nerve reconstruction in patients without spontaneous recovery of biceps function by three to six months of age, many recent studies suggest this may be unnecessary. In this study, the severity of glenohumeral dysplasia and shoulder function and strength in two groups of matched patients with a C5-6 lesion at a mean age of seven years (2.7 to 13.3) were investigated. One group (23 patients) underwent nerve reconstruction an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…Because of higher SD values of the brachialis and the biceps brachii, the elbow flexion can be seen later than expected. In parallel with our views, Nath and Liu claim that surgical interventions that performed between 3 and 6 months of age might impair the recovery potential of injured brachial plexus (Nath and Liu,2009). Our results suggest that the decision of surgical intervention in OBPP based on a certain time course might lead to wrong conclusions.…”
Section: Discussionsupporting
confidence: 75%
“…Because of higher SD values of the brachialis and the biceps brachii, the elbow flexion can be seen later than expected. In parallel with our views, Nath and Liu claim that surgical interventions that performed between 3 and 6 months of age might impair the recovery potential of injured brachial plexus (Nath and Liu,2009). Our results suggest that the decision of surgical intervention in OBPP based on a certain time course might lead to wrong conclusions.…”
Section: Discussionsupporting
confidence: 75%
“…These studies reported excellent results with botulinum toxin A combined with appropriate physiotherapy in those cases with co-contraction-related functional disabilities [14,25,26]. Some authors also described results of worsening of glenohumeral deformity in cases in which surgery was performed early for upper type palsies [27,28]. A better understanding of the co-contraction mechanisms between the shoulder abductors and adductors as well as the elbow flexors and extensors led some surgeons to re-evaluate their decisions about early nerve surgery based on elbow flexion or shoulder abduction.…”
Section: Discussionmentioning
confidence: 99%
“…Passive ranges of motion are always assessed before surgery and therefore should have yielded satisfactory ranges; however the postoperative gains (only 8.1° as compared to 45° and 48° for the other groups) were significantly less than expected. As mentioned above, Nath and Liu found that the glenohumeral deformity is worsened if the patient had a previous history of neural surgery [28], and a glenohumeral deformity may affect the external rotation more significantly than abduction. This may be evidence for the aforementioned study.…”
Section: Discussionmentioning
confidence: 99%
“…Although these procedures can improve function and stop the exacerbation of glenohumeral dysplasia, they have not been shown to stimulate joint remodeling [9]. A recent study by our institute showed that OBPI patients who underwent nerve reconstructions developed more serious shoulder complications and required more secondary surgical procedures to address these deformities [19]. Humeral osteotomy is commonly applied to treat OBPI and has been shown to improve shoulder position [20, 21].…”
Section: Discussionmentioning
confidence: 99%